Analysis of protein denaturation, and chemical visualisation, of frozen grass carp surimi containing soluble soybean polysaccharides. (17th June 2022) - Gao, Wenhong; Wu, Xinru; Ye, Ruisen; Zeng, Xin‐an; Brennan, Margaret A.; Brennan, Charles S.; Ma, Ji
Summary: The mechanism of protein denaturation of frozen surimi enriched with soluble soybean polysaccharides (SSPS) was investigated. Near‐infrared (NIR) and hyperspectral imaging (HSI) technology were used to predict protein denaturation. The fresh grass carp surimi was divided into four groups with SSPS additions of 0%, 1%, 3% and 5%, respectively, which were frozen and stored at −18 °C. Samples were examined after 0, 1, 2, 4 and 8 weeks, for salt‐soluble protein content, total SH, NIR hyperspectral image and Raman spectrum features. The results showed that addition of SSPS decelerated protein degradation. After 8 weeks of storage, the 5% SSPS addition maintained the highest salt‐soluble protein content, while for total SH, 3% and 5% SSPS addition had similar effect. Raman spectra illustrated that SSPS had the ability of maintaining an α ‐helix content, as well as decreasing the exposure of polar groups, and reducing the oxidation of SH group into disulphide bonds. NIR spectra showed that the overall reflectance of frozen surimi increased with the increase in SSPS. Two partial least squares regression (PLSR) models were established after pretreatment of HSI spectral statistics and selection of characteristic wavelengths. The distribution maps were finally generated based on the simplified PLSR models. Abstract : This graphical abstract shows the different quality of frozen surimi with or without SSPS, which was anaylsed by chemical detection, Raman spectrum, and NIR‐HSI.